2017
DOI: 10.1016/j.coisb.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Network-based approaches that exploit inferred transcription factor activity to analyze the impact of genetic variation on gene expression

Abstract: Over the past decade, a number of methods have emerged for inferring protein-level transcription factor activities in individual samples based on prior information about the structure of the gene regulatory network. We discuss how this has enabled new methods for dissecting trans-acting mechanisms that underpin genetic variation in gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The ability to infer molecular mechanisms distinguishes KPNNs from most methods for single-cell RNA-seq data analysis [ 102 , 103 ]. More generally, KPNNs provide a deep learning-based framework that complements existing bioinformatic methods for identifying key transcription factors [ 104 106 ] and other regulatory proteins [ 107 109 ] from single-cell gene expression data [ 110 , 111 ]. KPNNs are also complementary to well-established paradigms for mathematical modeling and computational simulation of signaling pathways and gene regulatory networks [ 46 , 47 , 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to infer molecular mechanisms distinguishes KPNNs from most methods for single-cell RNA-seq data analysis [ 102 , 103 ]. More generally, KPNNs provide a deep learning-based framework that complements existing bioinformatic methods for identifying key transcription factors [ 104 106 ] and other regulatory proteins [ 107 109 ] from single-cell gene expression data [ 110 , 111 ]. KPNNs are also complementary to well-established paradigms for mathematical modeling and computational simulation of signaling pathways and gene regulatory networks [ 46 , 47 , 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…The direct evidence is motivated by the idea that changes in transcription factor expression may lead to similar changes in in target gene expression. The coexpression of co-targeted genes is long established in the literature [ 9 , 10 ], and evidence also points to the coexpression of transcription factor genes with targets of that transcription factor [ 11 , 12 ]. Moreover, studies across multiple tissues have shown widely varying expression of transcription factor genes, indicating that this expression can be used to predict their regulatory involvement [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…In principle, TF activity inference could also be used to predict the transcriptomic effects of direct perturbations of TF activity levels, such as deletion or over-expression. Finally, inferred activity levels could be used to improve TF network mapping (5,12,14,16,(22)(23)(24)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…In principle, TF activity inference could also be used to predict the transcriptomic effects of direct perturbations of TF activity levels, such as deletion or over-expression of a TF-encoding gene. Finally, inferred activity levels could be used to improve TF network mapping ( Arrieta-Ortiz et al, 2015 ; Barenco et al, 2009 ; Bussemaker et al, 2001 , 2017 ; Cokus et al , 2006 ; Fu et al , 2011 ; Gao et al , 2004 ; Gitter et al , 2013 ; Lam et al, 2016 ; Lee and Bussemaker, 2010 ; Nachman et al , 2004 ; Shi et al , 2009 ; Tchourine et al , 2018 ; Wang et al, 2008 ; Yang et al, 2005 ; Yu and Li, 2005 ).…”
Section: Introductionmentioning
confidence: 99%